2013
DOI: 10.1111/cei.12175
|View full text |Cite
|
Sign up to set email alerts
|

Delayed post-injury administration of C5a improves regeneration and functional recovery after spinal cord injury in mice

Abstract: SummaryThe activation of a complement system can aggravate the secondary injury after spinal cord injury (SCI). However, it was reported recently that the activation of a complement could have both a secondary injury and a neuroprotective effect, in which C5a is the most important factor, but there is no direct evidence for this dual effect of C5a after SCI. In order to investigate the potential neuroprotective effect of C5a after SCI, in this study ectogenic C5a was injected intraperitoneally before/after SCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition, anaphylatoxins have been found to be essential in promoting tissue regeneration and repair in retina and CNS. 49,50 Staining with the C5b-9 antibody illustrated that when CR2-CD59 was administered, MAC was still able to form in the existing, although significantly smaller, wounds (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anaphylatoxins have been found to be essential in promoting tissue regeneration and repair in retina and CNS. 49,50 Staining with the C5b-9 antibody illustrated that when CR2-CD59 was administered, MAC was still able to form in the existing, although significantly smaller, wounds (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…According to the observation of Clark A., et al [ 42 ], it is suspected that complement C3 became active via plasmin (PLG) and thrombin (F7, F10, F2) proteases in a regenerative response. Regenerative effects of this pathway have also been evident in neurons [ 44 ], osteoblasts [ 45 ], and dental pulp progenitors [ 46 ]. It is, thus, expected that upregulation of C3 from the alternative pathway, C2 from both classical and lectin-dependent complement pathways highly increased the proteolytic cleavage of C3 to form C3b for mediating target clearance and forming C5 to C9 by associating with C3 convertase and finally initiating the assembly of the membrane attack complex as the regenerated cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, C3a and C5a activated NF- κ B/STAT-3 and enhanced hepatocyte regeneration after liver injury [ 59 ]. Recent reports showed that the delayed postinjury administration of C5a inhibited caspase-3 mediated neuron apoptosis leading to improved regeneration and functional recovery after murine spinal cord injury [ 60 ], as well as administration of C3a retina regeneration via STAT-3 activation in the progenitor cells present in the eye [ 61 ].…”
Section: Tissue Regeneration and Repairmentioning
confidence: 99%